Awaiting the heavenly country: the Civil War and America's culture of death - Schantz, Mark S. (Cornell University Press, 2008)
Emblems of mortality -- The heavenly country -- Melancholy pleasure -- A voice from the ruins -- Better to die free, than to live slaves -- The court of death